HUBUNGAN PROFIL PETERNAK DENGAN PENDAPATAN USAHA TERNAK KERBAU LUMPUR DI KECAMATAN LINTONG NIHUTA KABUPATENHUMBANG HASUNDUTAN - lia lumbantoruan (Universitas Sumatera Utara, 2014)
ABSTRACT NATALIA BR LUMBANTORUAN: Relationship of Farmer Profile and Income on Buffalo Revenue in the District Lintong Nihuta Humbang Hasundutan. The research was guided by MAR'UF TAFSIN and ARMYN HAKIM DAULAY The research was conducted in Lintong Nihuta, Hasundutan Humbang District, North Sumatra Province, which began on July 10 until August 29, 2012. The purpose of this study was to analyze the effect on the income profile of farmers in Lintong district buffaloes in district Nihuta Humbang Hasundutan. The method used is the method of survey respondents with a family unit that maintains buffaloes. The sampling method used is a Proportional Stratified Random Sampling is by selecting three villages namely Sitolu Bahal village, Nagasaribu Village 1, Village Sigumpar sample of this research were 55 families buffalo breeders obtained from 30% of farmers in each village, the village Sitolu Bahal (16 farmers), village Nagasaribu 1 (20 farmers), Sigumpar villages (19 farmers). Based on the research results obtained that the scale of business, education level breeder, breeding experience, number of dependents, level of generation farmer positive effect on increasing revenue buffalo breeders. While age negatively affect earnings breeder buffalo breeders in District Lintong District Nihuta Humbang Hasundutan. Keywords: Profile ranchers, farmers income, buffalo mud.